Navigating the Landscape of OTC Drug Utilization and Regulatory Challenges in India: Insights Review - George, Blessy K; Kumar, Jaidev; Kumar, Sunil; Ramaiah, Balakeshaw (International Journal of Pharmaceutical Investigation, 2026)
This review article on utilization and regulations of OTC drugs aims to highlight the significance of establishing legal policies on "OTC medicines" in India by outlining the potentially harmful effects of these medications on specific populations. The paper outlines OTC drug utilization and regulation in India, highlighting the need for a formal OTC drug category to establish a clear legal distinction between OTC and prescription drugs, enhancing regulatory clarity and market transparency. Strengthening pharmacovigilance is crucial for monitoring adverse events and drug interactions, while stricter controls are necessary to prevent counterfeit drugs. Regulating e-commerce and online pharmacies is also essential to ensuring the quality and safety of online drugs. Public education campaigns on safe self-medication are recommended to promote responsible usage and reduce adverse effects. A well-regulated OTC market can stimulate industry growth and innovation, allowing companies to develop new products while maintaining safety standards. Harmonising India’s OTC regulations with international standards will benefit both the domestic market and export potential, ensuring that Indian OTC drugs align with global safety and quality practices. India's OTC drug regulation is confusing due to the lack of formal classification, unclear guidelines for online sales, and inconsistent labeling standards. The growing e-commerce sector increases access, but lack of clear regulations poses risks of counterfeit products and unauthorised sales. Collaboration between regulators, the pharmaceutical industry, and consumers is crucial for promoting safe self-medication practices.
Keywords: Drug; Market; Over the Counter (OTC); Pharmaceutical; Policies; Regulation.